Probiotics-addicted low-protein diet for microbiota modulation in patients with advanced chronic kidney disease (ProLowCKD): A protocol of placebo-controlled randomized trial. (November 2020) - De Mauri, Andreana; Carrera, Deborah; Bagnati, Marco; Rolla, Roberta; Chiarinotti, Doriana; Mogna, Luca; Pane, Marco; Amoruso, Angela; Del Piano, Mario
Graphical abstract: Highlights: Untreated advanced renal failure results in the artificial replacement of the organ. Uremic syndrome alters the gut microbiota, and vice versa. A holistic approach must include a low protein diet. Adequate selected probiotics may support the nutritional therapy. Abstract: Microbiota is a term coined to describe the population of bacteria, viruses and fungi that inhabit in symbiosis within a living host. A connection between unbalanced microbiota and chronic kidney disease has been established. In these patients, high levels of urea reach the intestine promoting the overgrowth of bacterial species that are prone to generate uremic toxins. Due to the high morbidity and mortality of this condition, a large number of therapeutic approaches to reduce inflammation and microbial uremic toxins have been proposed, with controversial results. A low protein diet, with a protein intake of 0.6–0.8 g/kg of body weight, is a useful and historically pursued option with this regard. The aim of our study is to evaluate, among patients with advanced renal failure not on dialysis, the synergic beneficial effects of this diet and the selected probiotics Bifidobacterium longum (mix DLBL) and Lactobacillus reuteri LRE02 (DSM 23878).